STUDY ON READING LITERACY IN ELEMENTARY SCHOOLS: BIBLIOMETRIC ANALYSIS 2013-2023 - Fatma Rabia, Supriyati; Abdul Nasir Zakaria, Gamal; Alfi Muhimmah, Hitta; Hadi Wibowo, Amiruddin; Nurul (EduStream: Jurnal Pendidikan Dasar, 2024)
This study examines scholarly literature on reading literacy in elementary schools from 2013 to 2023 through bibliometric analysis. A total of 649 documents from the Scopus database were analyzed to identify research trends, geographic distribution, researcher collaborations, and frequently discussed topics. Findings indicate a significant increase in publications, particularly in the last five years, reflecting growing interest in reading literacy. The most cited article, “Closing the achievement gap through modification of neurocognitive and neuroendocrine function” by Blair & Raver (2014), highlights effective interventions in reading literacy. The journal “Reading Teacher” is the most productive source with 20 papers, and Florida State University is the most prolific institution. The United States contributes the most papers (326), showing leadership in this field. VOSviewer thematic mapping shows primary focuses on teaching practices, intervention effectiveness, and learning experiences. Density visualizations show that literacy practices, experiences, effects, and interventions are frequently researched themes. These findings offer valuable insights for researchers, educators, and policymakers to reimprove ading literacy in elementary schools, emphasizing the importance of institutional collaboration and evidence-based interventions in improving educational outcomes.